Incidence of Chronic Kidney Failure and Alcohol Consumption: Meta Analysis - Atmojo, Joko Tri; Yuliyanto, Dwi Joko; Hasanah, Yesi Ihdina Fityatal; Widiyanto, Aris; Anasulfalah, Hakim; Mubarok, Ahmad Syauqi (Journal for Quality in Public Health, 2024)
One of the main risk factors for chronic kidney disease (CKD) is excessive alcohol consumption. Alcohol consumption can damage the kidneys and disrupt their function because the kidneys filter toxins and waste products from the blood. This study aims to estimate the magnitude of the relationship between alcohol consumption and the incidence of chronic kidney failure. This research is a systematic review and meta analysis with PICO as follows, population: Adults. Intervention: alcohol consumption, Comparison: no alcohol consumption. Outcome: chronic failure events. The articles used in this research were obtained from three databases, namely Google Scholar, Pubmed, and Science Direct. Keywords to search for articles are "Alcohol" AND "Chronic Kidney Disease" OR CKD AND Multivariate. Articles used from 2018 – 2023. Article selection was carried out using the PRISMA flow diagram. Articles were analyzed using the Review Manager 5.3 application. A total of 6 cohort studies, namely Asia and Europe, were selected for systematic review and meta analysis. Cohort studies show that alcohol consumption influences the incidence of CKD. Patients who consume alcohol have a risk of experiencing CKD that is 1.05 times compared to those who do not consume alcohol, but the resulting increase in risk is not statistically significant (aHR= 1.04 95% CI= 0.85 to 1.27; p= 0.710). Forest Plot also shows heterogeneity of effect estimates between primary studies I2= 84%; p= 0.040, which means that the estimated effect between primary studies in this meta-analysis varies. Thus, the calculation of the average effect estimate was carried out using a random effect model approach.